Investigation into the microbial communities and associated crude oil-contamination along a Gulf War impacted groundwater system in Kuwait. (1st March 2020) - Bruckberger, Melanie C.; Morgan, Matthew J.; Bastow, Trevor P.; Walsh, Tom; Prommer, Henning; Mukhopadhyay, Amitabha; Kaksonen, Anna H.; Davis, Greg B.; Puzon, Geoffrey J.
Abstract: During the First Gulf War (1991) a large number of oil wells were destroyed and oil fires subsequently extinguished with seawater. As a result Kuwait's sparse fresh groundwater resources were severely contaminated with crude oil. Since then limited research has focused on the microbial community ecology of the groundwater and their impact on the associated contamination. Here, the microbial community ecology (bacterial, archaeal and eukaryotic) and how it relates to the characteristics of the hydrocarbon contaminants were examined for the first time since the 1991 event. This study was conducted using 15 wells along the main groundwater flow direction and detected several potential hydrocarbon degrading microorganisms such as Hyphomicrobiaceae, Porphyromonadaceae and Eurotiomycetes . The beta diversity of the microbial communities correlated significantly with total petroleum hydrocarbon (TPH) concentrations and salinity. The TPH consisted mainly of polar compounds present as an unresolved complex mixture (UCM) of a highly recalcitrant nature. Based on the proportions of TPH to dissolved organic carbon (DOC), the results indicate that some minor biodegradation has occurred within highly contaminated aquifer zones. However, overall the results from this study suggest that the observed variations in TPH concentrations among the sampled wells are mainly induced by mixing/dilution with pristine groundwater rather than by biodegradation of the contaminants. The findings make an important contribution to better understand the fate of the groundwater pollution in Kuwait, with important implications for the design of future remediation efforts. Graphical abstract: Image 1 Highlights: Bruckberger et al. Highlights. First investigation of microbial communities in 1st Gulf War impacted aquifers. Community structure correlated with contaminant (TPH & EC) concentrations. Biodegradation extent of the recalcitrant contaminant has remained minimal. Contaminant more impacted by dilution rather than significant biodegradation.